Pulsed electromagnetic gas valves for high-current plasma accelerators - Staltsov, V.V.; Chebotarev, V.V.; Herashchenko, S.S.; Kulik, N.V. (Вопросы атомной науки и техники, 2019)
The paper describes the design features of a gas valve for the axial (parallel to the axis of the accelerator) working gas supply into the accelerator channel. The results of gas-dynamic studies of the injectors are presented. The amount of the working gas inlet was investigated as a function of gas pressure under the blocking valve element. A strong dependence of the amount of the injected working gas on the electric current value in the control coil was found. Oписуються особливості конструкції клапана газу з електромагнітним приводом запираючого елемента для осьової (паралельної осі прискорювача) подачі газу в прискорювальний канал плазмодинамічних систем. Представлено результати газодинамічних досліджень клапана. Досліджена залежність кількості робочого газу, що напускається, залежно від тиску газу під запираючим елементом клапана. Показана істотна залежність кількості робочого газу, що напускається, від величини струму в електромагнітній котушці. Oписываются особенности конструкции клапана газа с электромагнитным приводом запирающего элемента для осевой (параллельной оси ускорителя) подачи рабочего газа в ускорительный канал плазмодинамических систем. Представлены результаты газодинамических исследований клапана. Исследована зависимость количества напускаемого рабочего газа в зависимости от давления газа под запирающим элементом клапана. Показана существенная зависимость количества инжектированного рабочего газа от величины тока в электромагнитной катушке.